2003
DOI: 10.1128/aac.47.2.620-625.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amphotericin B on Larval Growth of Echinococcus multilocularis

Abstract: Alveolar echinococcosis is caused by the parasitic cestode Echinococcus multilocularis. Benzimidazoles, namely, mebendazole and albendazole, are the only drugs available for the treatment of inoperable alveolar echinococcosis. At present, no therapeutic alternative is available for patients with progressive disease under treatment or for patients who are unable to tolerate the side effects of the benzimidazoles. In addition, benzimidazoles are only parasitostatic for E. multilocularis. Thus, new therapeutic op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 31 publications
0
51
0
1
Order By: Relevance
“…Amphotericin B (AMB) is the most effective drug for the treatment of visceral leishmaniasis (Murray, 2005) and it also acts against Trypanosoma (Yardley and Croft, 1999). Reuter et al (2003a) demonstrated that AMB is highly effective against E. multilocularis metacestodes in vitro, but only with a parasitostatic effect. The mode of AMB action is attributed to the selective and irreversible binding to sterols in cell membranes (Abu-Salah, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Amphotericin B (AMB) is the most effective drug for the treatment of visceral leishmaniasis (Murray, 2005) and it also acts against Trypanosoma (Yardley and Croft, 1999). Reuter et al (2003a) demonstrated that AMB is highly effective against E. multilocularis metacestodes in vitro, but only with a parasitostatic effect. The mode of AMB action is attributed to the selective and irreversible binding to sterols in cell membranes (Abu-Salah, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, alternatives to benzimidazoles are urgently needed. A novel potential chemotherapeutic option was recently discovered by demonstrating that AMB suppresses larval growth of E. multilocularis in vitro (26).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AMB (20,32) has an effect on membrane-bound enzymes (2) and binds to sterols, thereby forming transmembrane channels (1,8,9,31). It was clear from the beginning that AMB would have to be given permanently due to its parasitostatic effect on E. multilocularis larvae in vitro (26). In those experiments AMB was effective at concentrations between 0.625 and 2.5 g/ml, and benzimidazoles were used at 1 g/ml.…”
Section: Vol 47 2003 Amphotericin B In Human Alveolar Echinococcosimentioning
confidence: 99%
See 1 more Smart Citation
“…In a formulation as desoxycholate, it was shown to inhibit E. multilocularis larval growth in vitro and in human patients in vivo (Reuter et al, 2003a, b). Major drawbacks of AMB are its intravenous application mode and its nephrotoxic side-effects.…”
Section: Novel Chemotherapeutical Treatment Optionsmentioning
confidence: 99%